Environmental Campaign on the zerowaste.id Instagram Account to Educate the Community - Muhammad Alif; Lalita Hanief; Sri Astuty (Jurnal Riset Komunikasi (JURKOM), 2024)
Environmental campaigns are an effort to preserve the environment through various media. The aim of this research is to determine the environmental campaign on the Instagram account @zerowaste.id in educating the public. The method used in this research is interpretive qualitative. Data collection techniques use literature studies and documentation. Data analysis uses qualitative content analysis by interpreting @zerowaste.id account posts that are relevant to environmental campaigns. The research findings show that the Instagram account @zerowaste.id educates Instagram followers through its creative content in the form of how to make minimal waste hampers, alternative hair care products, zero waste healthy provisions, the benefits of compost for plants, facts about e-waste and zero challage. This environmental campaign aims to provide information to followers to reduce waste, apart from that, it also educates and persuades followers to use environmentally friendly products in their daily lives.